2018
DOI: 10.3177/jnsv.64.357
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fructo-Oligosaccharides on Gut Permeability and Inflammatory Responses in the Cecal Mucosa Quite Differs between Rats Fed Semi-Purified and Non-Purified Diets

Abstract: The effects of fructo-oligosaccharides (FOS) on gut-barrier function are still controversial in human and animal studies. Diet conditions would be a major factor for the controversy in animal studies. We fed rats a semi-purified (SP) or a non-purified diet (NP) with or without FOS (60 g/kg diet) for 9 (experiment 1) or 10 d (experiment 2). We assessed microbial fermentation, gut permeability, and inflammatory responses in the cecum (experiment 1), and mucus layer in the cecum, intestinal transit time and micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
8
1
Order By: Relevance
“…Contrary to what has been shown in other studies [60,61,62], cecal SCFA concentrations were reduced in prebiotic-consuming animals despite increases in Bifidobacterium taxa and greater cecal weight. However, one study demonstrated that prebiotic supplementation (fructo-oligosaccharide; FOS) with a nonpurified diet (chow) or semipurified diet (AIN-93) affected cecal SCFA concentrations differently as a result of alternative dietary ingredients in each formula [63]. Authors noted that nonpurified chow contained more nondigestible ingredients, including corn and wheat bran, whereas the semipurified diet contained refined and digestible ingredients, such as casein and corn oil, and may account for the reduced SCFA levels produced when FOS was added to the semipurified versus nonpurified diet [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to what has been shown in other studies [60,61,62], cecal SCFA concentrations were reduced in prebiotic-consuming animals despite increases in Bifidobacterium taxa and greater cecal weight. However, one study demonstrated that prebiotic supplementation (fructo-oligosaccharide; FOS) with a nonpurified diet (chow) or semipurified diet (AIN-93) affected cecal SCFA concentrations differently as a result of alternative dietary ingredients in each formula [63]. Authors noted that nonpurified chow contained more nondigestible ingredients, including corn and wheat bran, whereas the semipurified diet contained refined and digestible ingredients, such as casein and corn oil, and may account for the reduced SCFA levels produced when FOS was added to the semipurified versus nonpurified diet [63].…”
Section: Discussionmentioning
confidence: 99%
“…However, one study demonstrated that prebiotic supplementation (fructo-oligosaccharide; FOS) with a nonpurified diet (chow) or semipurified diet (AIN-93) affected cecal SCFA concentrations differently as a result of alternative dietary ingredients in each formula [63]. Authors noted that nonpurified chow contained more nondigestible ingredients, including corn and wheat bran, whereas the semipurified diet contained refined and digestible ingredients, such as casein and corn oil, and may account for the reduced SCFA levels produced when FOS was added to the semipurified versus nonpurified diet [63]. Therefore, our use of a prebiotic-enriched semipurified diet may have led to lower cecal SCFA concentration than normally expected.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to SCFAs, lactate and succinate might be produced after FOS fermentation. The gut permeability and inflammatory responses might be impacted due to stasis of the acidic environment [23].…”
Section: Discussionmentioning
confidence: 99%
“…Studying the response of microbial communities in the face of interference is critical to health (Costello et al, 2012), not only because the gut microbiota may change under disease conditions but also because the microbiota is affected by drugs administered to maintain host health . It is increasingly recognized that the therapeutic effects of natural products on disease may be achieved through drug-microbial interactions, indicating the importance of research into the effects of drugs on microbial metabolism (Genda et al, 2018). In this study, we first determined the changes in the structure and function of the gut microbiota in a rat model of CMG.…”
Section: Discussionmentioning
confidence: 99%